Lithium metal anodes, anode precursors for lithium metal anodes, and methods for producing anodes and anode precursors

By forming a thin metal layer on the lithium metal anode and coating a protective coating of carbon-based material and high-strength monomer polymer binder, the problem of shortening of life caused by dendrites is solved, and a lithium metal anode with high energy density and long life is achieved.

CN120359623APending Publication Date: 2025-07-22POSCO HLDG INC +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380085938.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-12-16
Filing Date
2023-12-13
Publication Date
2025-07-22

AI Technical Summary

Technical Problem

Existing lithium metal anodes are prone to dendrite growth during charging and discharging, resulting in shortening of life and insufficient energy density, making it difficult to achieve high energy density and long life at the same time.

Method used

A thin metal layer is formed on the current collector and a protective coating of a carbon-based material and a high-strength monomer polymer binder is coated on its surface. A lithium alloy layer is formed by electrodeposition, which inhibits dendrites from growing and increases lifetime.

Benefits of technology

The high energy density and extended life of the lithium metal anode are achieved, and the overall performance of the battery is improved by inhibiting dendrite growth and stabilizing lithium ion electrodeposition.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120359623A_ABST
    Figure CN120359623A_ABST
Patent Text Reader

Abstract

The invention relates to a lithium metal anode, an anode precursor for a lithium metal anode, and a method for producing an anode and an anode precursor. A lithium metal anode according to another aspect of the present invention includes a current collector, a metal layer formed on the current collector, and a protective coating layer formed on the metal layer, in which the metal layer contains a lithium alloy in an interface in contact with the protective coating layer, and the protective coating layer is a mixture of a carbon-based material and a binder, the binder may be a polymer obtained by polymerizing a high strength monomer grafted onto a high ionically conductive monomer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a lithium metal anode, a cathode precursor for a lithium metal anode, and methods for producing an anode and an anode precursor. Background Art

[0002] Lithium secondary batteries are mainly used for small batteries such as those for mobile phones, laptop computers, etc. Recently, with the increasing demand for medium and large batteries for batteries such as electric vehicles, there has been a demand for improving the energy density of lithium secondary batteries.

[0003] Therefore, lithium metal with a high specific capacity has attracted attention as an anode. However, in the case of a lithium metal anode, it is actually not easy to overcome the problem of shortened life due to dendrite growth, and this problem has not been completely solved. Summary of the Invention

[0004] Technical Problem

[0005] One aspect of the present disclosure is to provide a lithium metal anode having a high energy density and an extended life.

[0006] Another aspect of the present disclosure is to provide a precursor for manufacturing the above-described lithium metal anode.

[0007] Another aspect of the present disclosure is to provide a method for manufacturing the above-described lithium metal anode or the above-described precursor.

[0008] The subject matter of the present disclosure is not limited to the above. Any person of ordinary skill in the technical field to which the present disclosure pertains will not have difficulty understanding additional subject matters of the present disclosure from the overall content described in this specification.

[0009] Solution to the Problem

[0010] According to one aspect of the present disclosure, a precursor of a lithium metal anode includes a current collector, a metal layer formed on the current collector, and a protective coating formed on the metal layer, wherein the protective coating is a mixture of a carbon-based material and a binder, and the binder is a polymer obtained by polymerizing a high-strength monomer grafted onto a high-ion conductive monomer or a high-ion conductive polymer.

[0011] According to another aspect of the present disclosure, a lithium metal anode includes a current collector, a metal layer formed on the current collector, and a protective coating formed on the metal layer, wherein the metal layer contains a lithium alloy and lithium at an interface in contact with the protective coating, the protective coating is a mixture of a carbon-based material and a binder, and the binder is a polymer obtained by polymerizing a high-strength monomer grafted onto a high-ion conductive monomer or a high-ion conductive polymer.

[0012] According to another aspect of the present disclosure, a method for producing a lithium metal anode precursor includes: an operation of preparing a current collector; an operation of forming a metal layer on the surface of the current collector; and an operation of coating a slurry containing a carbon-based material, a binder, and a solvent on the surface of the metal layer and forming a protective coating, wherein the binder is a polymer obtained by polymerizing a high-strength monomer grafted onto a highly ion-conductive monomer or a highly ion-conductive polymer.

[0013] According to another aspect of the present disclosure, a method for manufacturing a lithium metal anode includes: an operation of preparing a current collector; an operation of forming a metal layer on the surface of the current collector; an operation of coating a slurry containing a carbon-based material, a binder, and a solvent on the surface of the metal layer and forming a protective coating; and an operation of electro-depositing lithium metal on the anode precursor, wherein the binder is a polymer obtained by polymerizing a high-strength monomer grafted onto a highly ion-conductive monomer or a highly ion-conductive polymer.

[0014] Advantageous Effects of the Invention

[0015] As described above, the present disclosure can provide an anode with high energy density and long life for a lithium secondary battery by forming a protective coating including a binder polymerized from grafted monomers on the lithium alloy layer of the thin film. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 is a scanning electron microscope image showing a cross-section of the anode precursor manufactured by Invention Example 1,

[0017] Figure 2 is an image showing the shape of the lithium metal anode manufactured by Invention Example 4,

[0018] Figure 3 Photographs of cross-sections of lithium metal anodes manufactured according to Invention Example 4 and Comparative Example 4 observed using a scanning electron microscope are provided.

[0019] Figure 4 is an image showing the results of comparing the bonding characteristics of Comparative Invention Example 4 and Comparative Example 4, and

[0020] Figure 5 is an asymmetric cell life graph of all-solid-state batteries manufactured using the anode of Invention Example 4 and the anode of Comparative Example 4. DETAILED DESCRIPTION

[0021] The embodiments of the present disclosure are not limited to the embodiments disclosed below. For example, those skilled in the art who understand the concept of the present disclosure will be able to easily propose other embodiments included within the scope of the concept of the present disclosure by adding, modifying, deleting components, etc., and this will also be regarded as included within the scope of the concept of the present disclosure.

[0022] In addition, throughout the specification, unless otherwise specified, the term "comprising" a component means that other components may be included, rather than excluding other components.

[0023] In addition, it should be noted that, unless otherwise specified in the present disclosure, the mixing ratio or composition is based on weight.

[0024] In addition, each example of the implementation modes described below is only an example for implementing the technical concept of the present disclosure, and the scope of the rights of the present disclosure is not limited to each example of the implementation mode.

[0025] Hereinafter, the present disclosure will be described in detail.

[0026] In order to maximize the energy density of the battery, the strategy of reducing the lithium thickness to 20 μm or less for ultrathin lithium metal is crucial. However, there are still many difficulties in manufacturing thinner lithium metal through commercial processes, and lithium metal anodes are problematic due to non-uniform current density and dendrite growth caused by electrochemical reactions during the charge and discharge processes of secondary batteries. This may trigger continuous side reactions with the electrolyte and ultimately lead to an internal short circuit where the anode and cathode come into contact. Such dendrite growth may also cause serious problems in terms of low life characteristics and stability. For this reason, it is difficult to practically utilize ultrathin lithium metal anodes.

[0027] Various methods have been proposed to suppress such lithium dendrites and increase the life, but it is still difficult to simultaneously achieve high energy density and sufficient life characteristics with ultrathin lithium.

[0028] The inventors of the present disclosure have confirmed that, according to an embodiment of the present disclosure, a thin lithium-friendly metal layer is formed on the surface of the current collector, and this metal layer is effective in suppressing the growth of lithium dendrites, alloying with lithium, and improving the life. However, the above process is only one advantageous process according to the present disclosure and is not necessarily limited thereto, and a thin metal layer in the form of an alloy may also be formed from the beginning.

[0029] In addition, according to an embodiment of the present disclosure, a protective coating may be formed on the surface of the metal layer. Since the protective coating has excellent ion transfer function and structural stability, it can enable lithium ions to be stably electrodeposited on the thin-film metal layer and form an alloy, and can help improve the charge / discharge life by preventing direct contact between the electrolyte and the lithium metal.

[0030] Therefore, the anode precursor according to an embodiment of the present disclosure is a preliminary product to be processed into a lithium metal anode by subsequent electrodeposition of lithium metal, and may include a current collector, a metal layer formed on the current collector, and a protective coating formed on the metal layer.

[0031] The current collector can be any material used as a current collector for a lithium secondary battery, and thus its material and thickness are not particularly limited, and any material and thickness that can be used in the technical field to which the present disclosure pertains can be used. However, as some examples that do not limit the present disclosure, copper (Cu), nickel (Ni), stainless steel, and Invar alloy can be used, and a foil-shaped current collector can be used.

[0032] In addition, the metal layer of the present disclosure does not contain lithium, but can be used because the metal layer has a high affinity for lithium and can be alloyed. By using such a metal, the lithium metal anode obtained later can include a lithium alloy layer. Metals that can be alloyed with lithium include Al, In, Ag, Au, Zn, Mg, Si, etc., and these metals can be used alone or as alloys of two or more types.

[0033] By limiting the metal layer to a thin thickness, the thickness of the alloy layer formed later by alloying can be made thin. When the thickness of the alloy layer is made thin in this way, the energy density, meaning the amount of energy per unit weight, can increase. Considering these points, in an embodiment of the present disclosure, the thickness of the metal layer can be limited to 5 μm or less. To increase the energy density and suppress the problem of volume expansion, the thinner the thickness, the more advantageous. However, if the thickness is too thin, the uniformity of the metal layer may be poor, which may limit the effective formation of the lithium alloy. Therefore, in an embodiment of the present disclosure, the thickness of the metal layer can be limited to 10 nm or more. A more preferred thickness of the metal layer can be 100 nm to 500 nm.

[0034] In addition, the protective coating according to an embodiment of the present disclosure can be a mixture of a carbon-based material and a binder. The carbon-based material can be, but is not necessarily limited to, amorphous carbon such as furnace black, acetylene black, ketjen black, graphene, etc. In addition, the binder can be a polymer obtained by polymerizing a high-strength monomer grafted onto a high-ion conductive monomer or a high-ion conductive polymer. When the high-strength monomer is grafted onto the high-ion conductive polymer, a part of the high-strength monomer can be polymerized during the polymerization treatment after grafting. When a polymer is formed in this way after grafting monomers having two characteristics, the physical / chemical properties of each monomer can be effectively utilized, and thus, the protective coating can be stably bonded to the electrode, and excellent electrochemical characteristics can be achieved. In addition, according to an embodiment of the present disclosure, after forming the above protective coating, lithium can be electrodeposited by an electroplating process. In this case, lithium can be easily transferred to the metal layer on the bottom of the protective coating, and alloying can occur. This easy ion transfer characteristic may be advantageous for the charging and replenishment of lithium ions as a lithium metal anode.

[0035] In addition, when lithium ions are not easily transferred into the protective coating, lithium may accumulate on the surface of the protective coating during the lithium electrodeposition process or the battery charging process, thus easily forming dendrites. However, in the case of the anode provided in the embodiments of the present disclosure, lithium ions can be easily transferred to the bottom of the protective coating through the highly ion-conductive binder and the lithium metal alloy layer contained in the protective coating, so that the growth of dendrites is effectively suppressed.

[0036] The highly ion-conductive monomer of the binder contained in the protective coating is not particularly limited as long as it is easy to conduct ions. However, in the embodiments of the present disclosure, it may be one or both or more selected from the following: vinyl acetate, ethylene glycol, aniline, ethylenimine, acrylonitrile, pyromellitic dianhydride, 4,4-diaminodiphenyl ether, 3,4-dihydroxyphenylethylamine, hexahydroxymethylmelamine, methyl cyanoacrylate, isophorone diisocyanate, and methylene diphenyl diisocyanate. The highly ion-conductive polymer that can be contained in the protective coating may be a polymer of the monomer.

[0037] In addition, the high-strength monomer may be one or both or more selected from the following: acrylic acid, ethylene, propylene, styrene, methyl methacrylate, carbonic acid, vinyl chloride, phosgene, oxalic acid, and succinic acid.

[0038] At this time, the highly ion-conductive monomer may be contained at a ratio of 0.25 moles to 2 moles per 1 mole of the high-strength monomer. When grafting the high-strength monomer using the highly ion-conductive polymer as a starting material, the ratio of the moles of the monomer contained in the polymer to the moles of the high-strength monomer may be within the above range. When added at the above ratio, optimal bonding stability can be obtained.

[0039] The protective coating may have a thickness of 1 μm to 20 μm. By ensuring a thickness of 1 μm or more, the structure can be maintained during the lithium metal electrodeposition process, and by setting the thickness to 20 μm or less, an excessive increase in the interlayer resistance is prevented, so that the lithium metal can be easily transferred under the protective coating, and the battery density can also be advantageously ensured. A more preferable thickness of the protective coating may be 5 μm to 10 μm. When lithium metal is electrodeposited on the precursor to obtain the anode, the thickness of the entire anode layer including the protective layer (for example, the sum of the thicknesses of the metal layer and the protective layer) may be about 2 μm to 30 μm, and preferably may be in the range of 10 μm to 25 μm.

[0040] The protective coating described above may have a porosity of 40% or higher. If the porosity is too small, it is difficult to impregnate the plating solution when electroplating lithium to fabricate the lithium metal anode described below, and thus lithium metal may precipitate on the upper surface of the protective coating. Therefore, the larger the porosity, the more advantageous it is, but considering the structural stability, the porosity can be limited to 80% or lower. The porosity can be measured, for example, by taking a photograph of the cross-section of the polished protective coating using an ion beam device (as in Figure 1 ), and using an image analysis program to calculate the area of the pore region relative to the total area.

[0041] In another embodiment of the present disclosure, a lithium metal anode may be provided.

[0042] The lithium metal anode according to an embodiment of the present disclosure may include a current collector, a metal layer formed on the current collector, and a protective coating formed on the metal layer, and the metal layer may contain a lithium alloy and lithium at the interface in contact with the protective coating.

[0043] According to an embodiment of the present disclosure, the lithium alloy may be an alloy of metallic lithium and one or two or more selected from Al, In, Ag, Au, Zn, Mg, Si, etc.

[0044] The lithium metal anode can be fabricated from the anode precursor described above, but it can also be fabricated by other methods. For example, the lithium metal anode can be fabricated by forming a separate alloy on the current collector and then forming a protective layer on the current collector, and any other possible method can be used to fabricate the lithium metal anode of the present disclosure.

[0045] Hereinafter, methods for fabricating the anode precursor and the lithium metal anode of the present disclosure will be described. However, the fabrication methods described below are only a preferred example for fabricating the anode precursor and the lithium metal anode of the present disclosure, and do not mean that the anode precursor or the lithium metal anode of the present disclosure should be fabricated by the following methods.

[0046] First, an operation of forming a metal layer on the surface of the current collector can be performed. There is no particular limitation on the method of forming the metal layer, and various methods such as electroplating, deposition, transfer, etc. can be used.

[0047] Thereafter, a slurry containing a carbon-based material, a binder, and a solvent is coated on the surface of the metal layer and dried to form a protective coating, thereby obtaining an anode precursor.

[0048] According to an embodiment of the present disclosure, the mixing ratio of the carbon-based material and the binder can be adjusted such that the ratio of the binder is 3% to 15% of the total weight of the carbon-based material and the binder. The amount of the solvent is not particularly limited and can be mixed to such an extent that the slurry can have a viscosity suitable for coating. However, in an embodiment of the present disclosure, the solvent can be added at a weight ratio of about 8 to 10 times the total solid content, including the solid content in all carbon-based materials, binders, etc. The above binder can be a polymer obtained by polymerizing a high-strength monomer grafted onto a highly ion-conductive monomer or a highly ion-conductive polymer.

[0049] According to an embodiment of the present disclosure, a lithium metal anode can be prepared by preparing an anode precursor and then electrodepositing lithium metal on the anode precursor, which includes a current collector, a metal layer formed on the current collector, and a protective coating formed on the metal layer. The process of electrodepositing lithium metal can be carried out by an electrolytic plating method.

[0050] Embodiments of the invention

[0051] (Example)

[0052] Hereinafter, the present disclosure will be specifically described by way of examples. However, it should be noted that the following examples are intended to illustrate and embody the present disclosure, and are not intended to limit the scope of the rights of the present disclosure. This is because the scope of the rights of the present disclosure is determined by the matters described in the patent claims and the matters reasonably inferred therefrom.

[0053] Preliminary Experiment - Bond Strength Test of the Protective Coating

[0054] The following experiments were conducted to test the adhesion strength of the protective coating according to the binder type and content. That is, a polymer (PVA-g-PAA) was obtained as a binder (Preliminary Experiments 1 to 4) by polymerizing an acrylic monomer (high-strength monomer) grafted onto polyvinyl acetate (high ionic conductive polymer). At this time, for each experiment, the number of moles of vinyl acetate monomer added per 1 mole of acrylic monomer contained in polyvinyl acetate was changed from 0.25 to 2. However, in the case of Comparative Experiment 1, instead of the polymer of the high ionic conductive monomer grafted with the high-strength monomer, a mixture of SBR (styrene-butadiene rubber) and CMC (carboxymethyl cellulose) with a weight ratio of 1:2 was used as the binder. Each binder was coated on one side of the current collector to form a polymer film, and dried at a temperature of 130°3 or higher to sufficiently remove the solvent. Then, the adhesion strength between the current collector and the polymer film was measured by a peel test, and the results are shown in Table 1. The peel test was conducted as follows: a peel tape was adhered to the polymer film, and the adhesion strength was measured while the tape was peeled off from the polymer film layer at a set speed using a UTM (universal testing machine, Petrol Lab.DA-01). In Table 1, the adhesion strength A is the result when the peel speed is 5 mm / min, and the adhesion strength B is the result when the peel speed is 200 mm / min.

[0055] [Table 1]

[0056]

[0057] As examined above, when the high-strength monomer grafted onto the high ionic conductive polymer according to an embodiment of the present disclosure is polymerized, a high adhesion strength is obtained. In particular, when the molar ratio of the high ionic conductive monomer per 1 mole of the high-strength monomer is between 0.25 and 2, the adhesion strength is excellent, and it is confirmed that the adhesion strength is optimal when the value is 1. Comparative Experiments 2 and 3 are cases where the monomer ratio exceeds the range specified in the present disclosure, and show a poorer adhesion strength compared to the adhesion strength of the inventive examples.

[0058] Manufacture of Anode Precursors

[0059] Prepare a copper current collector, and form silver on the current collector by electroless plating to a thickness of about 300 nm. In all examples except Comparative Example 3, prepare PVA-g-PAA (the binder of Preliminary Experiment 3) in which the molar ratio of vinyl acetate monomer and acrylic monomer is 1:1 as the binder, and in the case of Comparative Example 3, use the binder prepared by Comparative Experiment 1. Mix the binder, carbon black, and water to prepare a slurry. Adjust the mixing ratio of water in the slurry so that the slurry has a viscosity suitable for coating, and adjust the ratio of carbon black and binder for each example as shown in Table 2. Coat the slurry on the current collector using a doctor blade and dry it at 100 °C for 10 minutes. Thereafter, vacuum dry the slurry for an additional 3 hours to form a protective coating. Confirm that the protective coating has a thickness of about 5 μm in all examples. The porosity of the protective coating in the table is measured by taking a photograph of the polished cross-section of the protective coating using an ion beam device and calculating the area of the pores relative to the total area using an image analysis program.

[0060] [Table 2]

[0061]

[0062] In the case of Comparative Example 1 in Table 2 above, since the protective coating did not adhere to the extent that it was difficult to measure the adhesion strength, the values of the adhesion strength and porosity were not separately indicated. As can be seen from the results in Table 2, when the binder content is too low, the protective coating cannot adhere to the metal layer on the upper side of the current collector with sufficient adhesion strength. Therefore, in order to have a certain degree of sufficient adhesion strength, the ratio of the binder to carbon black in the binder needs to be 3% or higher, and more preferably 6% or higher. However, it was confirmed that when the binder content exceeds 15% and reaches 20%, the adhesion strength is excellent, but the porosity of the electrode becomes too low. Therefore, in the embodiments of the present disclosure, the preferred binder content in the protective coating can be set to 15% or lower. Figure 1 The cross-section of the anode precursor manufactured by Invention Example 1 is shown. As can be seen in the figure, the thickness of the protective coating is about 5 μm, and it was confirmed that sufficient pores were formed in the protective coating.

[0063] Manufacture of Lithium Metal Anodes

[0064] Invention Example 4

[0065] Lithium electrolytic electroplating was performed on the anode precursor prepared according to Invention Example 2 above. During electroplating, a lithium metal foil with a thickness of 500 μm was used as the counter electrode, and the electrodeposition solution contained lithium bis(fluorosulfonyl)imide and 1,2-dimethoxyethanol at proportions of 30 wt% and 68 wt% respectively, and additionally contained lithium nitrate and fluoroethylene carbonate each in an amount of 1 wt%. The counter electrode was attached to a copper current collector while being insulated from the anode precursor and immersed in the electrodeposition solution. Thereafter, lithium was electrolytically electroplated onto the metal layer of the anode precursor by applying a constant current. At this time, the applied current density was 4 mA / cm 2 , and a lithium alloy layer and a lithium metal layer with a thickness of about 10 μm were formed. The shape of the lithium metal anode obtained by the above treatment is shown in Figure 2 .

[0066] Comparative Example 4

[0067] A lithium metal anode was manufactured in the same manner as in Invention Example 4, except that the anode precursor manufactured by Comparative Example 3 was used.

[0068] In Figure 3 are shown photographs of cross-sections of the lithium metal anodes manufactured by Invention Example 4 and Comparative Example 4.

[0069] Figure 4 Show the results of comparing the adhesion characteristics of Invention Example 4 and Comparative Example 4. To evaluate the adhesion characteristics, a tape (3M Magic 810D) was adhered to the surface of the protective coating of the anode on which lithium was electrodeposited in a glove box and separated from the surface, and the condition of the remaining protective coating was evaluated while separating. As can be seen in the figure, in the case of the lithium metal anode manufactured by Invention Example 4, the protective coating remained on the electrode even after testing, while in the case of the lithium metal anode manufactured by Comparative Example 4, most of the protective coating was lost.

[0070] Battery Life Evaluation

[0071] All-solid-state batteries were manufactured using the lithium metal anodes provided by Invention Example 4 and Comparative Example 4 mentioned above, and the life characteristics of the solid-state batteries were evaluated.

[0072] A lithium indium alloy (500 μm thick) was used as the counter electrode in the battery, and a sulfide-based argyrodite (700 μm thick) was used as the solid electrolyte. During battery assembly, the solid electrolyte was pressurized to 370 Mpa to form a dense electrolyte, and then the working electrode and the counter electrode were attached to both sides of the solid electrolyte under a pressure of 50 MPa to complete battery assembly. In a pressurized environment of 16 Mpa, at a current density of 1 mA / cm 2 and 1 mAh / cm 2Perform life evaluation under the conditions of charge / discharge capacity. Table 3 below compares the lives of electrodes including anodes fabricated by each example. The electrode life is expressed as the number of cycles before short circuit occurs.

[0073] [Table 3]

[0074] Differentiation Life (Number of Cycles) Inventive Example 4 819 Comparative Example 4 458

[0075] As can be seen from Table 3 above, compared with a battery including a lithium metal anode fabricated by a comparative example according to conditions deviating from the present disclosure, a battery including a lithium metal anode fabricated according to the conditions provided in the embodiments of the present disclosure shows an effect of increasing the life by about 80%. Figure 5 Shows the asymmetric cell life graph of all-solid-state batteries fabricated using the anode of Invention Example 4 and the anode of Comparative Example 4. As can be seen from the figure, in the case of Comparative Example 4, the life ends after about 900 hours, but Invention Example 4 has a life close to 1600 hours.

[0076] Therefore, the advantageous effects of the present disclosure can be confirmed.

Claims

1. An anode precursor, comprising: a current collector, a metal layer formed on the current collector; and a protective coating formed on the metal layer, wherein the protective coating is a mixture of a carbon-based material and a binder, and the binder is a polymer obtained by polymerizing a high-strength monomer grafted onto a highly ion-conductive monomer or a highly ion-conductive polymer.

2. The anode precursor according to claim 1, wherein The metal layer has a thickness of 10 nm to 5 μm.

3. The anode precursor according to claim 1, wherein, The metal layer comprises one or two selected from Al, In, Ag, Au, Zn, Mg, and Si.

4. The anode precursor according to claim 1, wherein The protective coating has a thickness of 1 μm to 20 μm.

5. The anode precursor according to claim 1, wherein The protective coating has a porosity of 40% or higher.

6. The anode precursor according to claim 1, wherein, The highly ion-conductive monomer is included in a ratio of 0.25 mol to 2 mol per 1 mol of the high-strength monomer.

7. A lithium metal anode, comprising: a current collector, a metal layer formed on the current collector; and a protective coating formed on the metal layer, wherein the metal layer contains a lithium alloy at an interface in contact with the protective coating, the protective coating is a mixture of a carbon-based material and a binder, and the binder is a polymer obtained by polymerizing a high-strength monomer grafted onto a highly ion-conductive monomer or a highly ion-conductive polymer.

8. The lithium metal anode according to claim 7, wherein, The highly ion-conductive monomer is one or two or more selected from the following: vinyl acetate, ethylene glycol, aniline, ethylenimine, acrylonitrile, pyromellitic dianhydride, 4,4-diaminodiphenyl ether, 3,4-dihydroxyphenylethylamine, hexahydroxymethylmelamine, methyl cyanoacrylate, isophorone diisocyanate, and methylene diphenyl diisocyanate, and the highly ion-conductive polymer is a polymer obtained by polymerizing the highly ion-conductive monomer.

9. The lithium metal anode according to claim 7, wherein The high-strength monomer is one or two or more selected from the following: acrylic acid, ethylene, propylene, styrene, methyl methacrylate, carbonic acid, vinyl chloride, phosgene, oxalic acid, and succinic acid.

10. The lithium metal anode according to claim 7, wherein, The highly ion-conductive monomer is included in a ratio of 0.25 mol to 2 mol per 1 mol of the high-strength monomer.

11. The lithium metal anode according to claim 7, wherein, The lithium alloy is an alloy of one or two or more selected from Al, In, Ag, Au, Zn, Mg, and Si.

12. The lithium metal anode according to claim 7, wherein, The metal layer further comprises lithium metal.

13. The lithium metal anode according to claim 7, wherein, The sum of the thicknesses of the metal layer and the protective coating is 2 μm to 30 μm.

14. A method for producing an anode precursor, the method comprising: an operation of preparing a current collector; an operation of forming a metal layer on the surface of the current collector; and an operation of coating a slurry containing a carbon-based material, a binder, and a solvent on the surface of the metal layer and forming a protective coating, wherein the binder is a polymer obtained by polymerizing a high-strength monomer grafted onto a highly ion-conductive monomer.

15. The method for producing an anode precursor according to claim 7, wherein, The highly ion-conductive monomer is included in a ratio of 0.25 mol to 2 mol per 1 mol of the high-strength monomer.

16. A method for manufacturing a lithium metal anode, comprising: an operation of preparing a current collector; an operation of forming a metal layer on the surface of the current collector; an operation of coating a slurry containing a carbon-based material, a binder, and a solvent on the surface of the metal layer and forming a protective coating; and The operation of electro-depositing lithium metal on the anode precursor wherein the binder is a polymer obtained by polymerizing a high-strength monomer grafted onto a high-ion conductive monomer.

17. The method for manufacturing a lithium metal anode according to claim 16, wherein, The high-ion conductive monomer is one or both or more selected from the following: vinyl acetate, ethylene glycol, aniline, ethylenimine, acrylonitrile, pyromellitic dianhydride, 4,4-diaminodiphenyl ether, 3,4-dihydroxyphenylethylamine, hexahydroxymethylmelamine, methyl cyanoacrylate, isophorone diisocyanate and methylene diphenyl diisocyanate, and the high-ion conductive polymer is a polymer obtained by polymerizing the high-ion conductive monomer.

18. The method for manufacturing a lithium metal anode according to claim 16, wherein, The high-strength monomer is one or both or more selected from the following: acrylic acid, ethylene, propylene, styrene, methyl methacrylate, carbonic acid, vinyl chloride, phosgene, oxalic acid and succinic acid.

19. The method for manufacturing a lithium metal anode according to claim 16, wherein, The weight ratio of the binder to the total weight of the carbon-based material and the binder is 3% to 15%.

20. The lithium metal anode according to claim 16, wherein, The high-ion conductive monomer is included at a ratio of 0.25 moles to 2 moles per 1 mole of the high-strength monomer.